Educação permanente ou intermitente? explorando a realidade dos médicos da Atenção Primária de Campina Grande/PB - Freitas, Paula Falcão Carvalho Porto de (2018)
The objective of this work was to analyze the implementation of the National Policy on Permanent Education in Health (PNEPS) in Primary Health Care (APS) in the city of Campina Grande, Paraíba (PB). Therefore, the study was developed using two strategies. The first one was accomplished through an integrative review in the literature through researches in the SciELO databases, using the following Descriptors in Health Sciences (DeCS): Permanent education; Primary Health Care; Telehealth. In order to select the articles, the following criteria were established: articles in Portuguese, English or Spanish, with a restriction on national production, with a title related to PNEPS in APS, as of 2010 because in Brazil, PNEPS was started in 2004, updated in 2007 and revised in 2009. The second policy analysis strategy was based on the evaluation of its implementation in Campina Grande / PB through a questionnaire applied to the Family Health Strategy (ESF) physicians. Two articles were drafted and submitted to the Pan American Health Organization (PAHO) Journal. The first one followed the rules of an opinion article that concluded that the PNEPS implemented would be able to produce dialogue and cooperation between professionals, between services and between management, attention, training and social control, so that these areas could be strengthened and expanded the ability of everyone to tackle and solve problems with quality. It would also contribute to the team's analysis of their own relationships and their work process, which is traversed by diverse institutions. The second article showed that only 31% of the physicians in Campina Grande who work in the Family Health Strategy (ESF) knew the PNEPS, and only one had actually read the ordinance in question, although it presented difficulties for its use as all others . Similar to the national scenario, there is no support from local management, which may correspond to micropolitical issues, as well as questions related to the training of these professionals that are not exposed to the daily life of the PHC satisfactorily during graduation, which impairs the practice of a critical-reflexive attitude needed when acting in health.